The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1093/hmg/8.12.2303
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations and Genotype-Phenotype Relationships in 107 Families With Fukuyama-Type Congenital Muscular Dystrophy (FCMD)

Abstract: Fukuyama-type congenital muscular dystrophy (FCMD), one of the most common autosomal recessive disorders in the Japanese population, is characterized by congenital muscular dystrophy in combination with cortical dysgenesis (micropolygyria). Recently, we identified, on chromosome 9q31, the gene responsible for FCMD, which encodes a novel 461 amino acid protein which we have termed fukutin. Most FCMD-bearing chromosomes examined to date (87%) have been derived from a single ancestral founder, whose mutation cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 17 publications
7
114
1
1
Order By: Relevance
“…In comparison with our study, systematic analysis of the FCMD gene in 107 unrelated patients by Kondo-Iida et al (1999) revealed that 80 probands (75%) were homozygous for the 3 kb insertion, 25 (23%) were heterozygous, and two did not show the 3 kb insertion on either allele. In our study, however, the number of homozygotes and heterozygotes was almost the same.…”
Section: Phenotype-genotype Relationship In Fcmd After Discovery Of Fcontrasting
confidence: 73%
See 1 more Smart Citation
“…In comparison with our study, systematic analysis of the FCMD gene in 107 unrelated patients by Kondo-Iida et al (1999) revealed that 80 probands (75%) were homozygous for the 3 kb insertion, 25 (23%) were heterozygous, and two did not show the 3 kb insertion on either allele. In our study, however, the number of homozygotes and heterozygotes was almost the same.…”
Section: Phenotype-genotype Relationship In Fcmd After Discovery Of Fcontrasting
confidence: 73%
“…According to the report by Kondo-Iida et al (1999), among patients homozygous for the founder mutation, 91.5% showed milder (stand or walk with or without support) or typical (able to sit unassisted or to slide on buttocks) phenotypes, and only 2.5% of cases were classified as severe (could sit only with support or had no head control), while among patients with heterozygous for the founder mutation, 92% showed severe phenotypes. This was true in our study, as most homozygotes could sit without help, while half of the heterozygotes were bedridden.…”
Section: Phenotype-genotype Relationship In Fcmd After Discovery Of Fmentioning
confidence: 99%
“…This insertion, which occurs in the 3' untranslated region of the gene, causes reduced expression of normal fukutin protein, resulting in a milder phenotype than would occur from a null mutation. Once compound heterozygotes were identified, the clinical spectrum was expanded to include ocular defects and a poorer prognosis, 24 and homozygous nonsense mutations were shown to yield WWS. 25 Likewise, mutations in POMT1 were originally reported only to give rise to WWS, which presents with the most severe clinical features of all the dystroglycanopathies (the average life expectancy of WWS patients is 0.8 years).…”
Section: The Dystroglycanopathies: Clinical and Genetic Findingsmentioning
confidence: 99%
“…51) Fukutin (FKTN, 607440) is essential for the protein complex between dystrophin and dystroglycan, to preserve glycosyltransferase activity, and fukutin-related protein (FKRP, 606596) can regulate the post-translational modification of dystroglycan. [52][53][54] Missense mutations such as Q358P and R179T mutations in the FKTN gene, as well as insertion of a 3,062-bp transposon situated in the 3-prime untranslated region of the FKTN gene, can cause a less diagnosed form of idiopathic dilated cardiomyopathy and congestive heart failure [52][53][54] Mutations in the FKRP gene cause a phenotypic spectrum arising from limb-girdle muscular dystrophy with dcM. 15,55,56) 4.…”
Section: )mentioning
confidence: 99%